The Management of Medical Services in the Early and Late Phase of Tsunami: A Preparation for Humanitarian Health Assistance - Sutiono, Agung Budi; Murni, Tri Wahyu; Qiantori, Andri; Suwa, Hirohiko; Ohta, Toshizumi (IntechOpen, 2011)
None